Heinrich 0 on the east Canadian margin: Source, distribution, and timing. (16th December 2015) - Pearce, C.; Andrews, J. T.; Bouloubassi, I.; Hillaire‐Marcel, C.; Jennings, A. E.; Olsen, J.; Kuijpers, A.; Seidenkrantz, M.‐S.
Abstract: The last deglaciation was marked by intervals of rapid climatic fluctuations accompanied by glacial advances and retreats along the eastern margin of the Laurentide Ice Sheet. One of these climatic events, the Younger Dryas cold reversal, was accompanied by a detrital carbonate event referred to as "Heinrich event 0" (H0) that deposited ice‐rafted debris and especially detrital carbonate‐rich (DC) sediment layers in the western and southern Labrador Sea. The precise age, duration, source, and geographical distribution of the H0 DC event, however, are not entirely clear. A high‐sedimentation rate sequence cored off southern Newfoundland yielded an age of 11.5–11.3 calibrated kyr B.P. for this layer, thus pointing to its deposition directly following the Younger Dryas termination, likely associated with rapid ice retreat and warming at the onset of the Holocene. At the study site, the H0 layer contains increased concentrations of detrital carbonates (calcite/dolomite ratio 2.5:1) and a mature biomarker composition, similar to that found in Heinrich Layers 1, 2, 4, and 5, which together suggest an origin from Hudson Strait. Grain size analysis indicates that the H0‐sediments were transported to the study site mostly through shallow plumes along the Labrador Shelf, with some hyperpycnal dispersal, deeper, along the slope and rise. Our data thus point to a large meltwater release caused by retreat of the ice margin in the Hudson Strait area. The relvatively short duration of the H0 layer, and its timing right after a major climatic transition, combined with its ubiquitous regional occurrence makes it valuable for correlating different sediment records from the western Labrador Sea. Key Points: An H0 layer is studied from Southern Newfoundland Biomarkers and mineralogy indicate a Hudson Strait source The H0 event is linked to rapid ice retreat at the onset of the Holocene